Bladder Management With Epidural Anesthesia During Labor: A Randomized Controlled Trial. Issue 4 (July 2015) - Wilson, Barbara L.; Passante, Tammy; Rauschenbach, Diane; Yang, Rumei; Wong, Bob
Abstract: Purpose: Many labor nurses routinely include continuous urinary catheterization (CC) as part of their standard care for women who receive intrapartum epidural anesthesia, to prevent urinary retention, thought to delay fetal descent. Recent studies question use of CCs during labor, as they may predispose patients to urinary tract infections (UTIs), even though the catheters are in place for a relatively short period of time. The objective of this study was to determine the influence of CCs versus intermittent catheters (ICs) (only as needed) on the duration of second stage of labor and the incidence of postpartum UTIs. Study Design and Methods: Randomized controlled trial. English-speaking low-risk nulliparous women ≥37 weeks gestation with a single fetus in a vertex presentation who requested an epidural were eligible for participation. Prior to epidural placement, cervical status was documented, women were encouraged to void, and then women were randomized to receive either CC or IC as the method for urinary bladder management for the duration of the first stage of labor. Final sample size included 123 participants; 55 in the CC group and 68 in the IC group. Results: No differences were noted in length of second stage labor, and the overall incidence of UTIs in both groups was low. There was a significantly increased likelihood of cesarean birth in women who had CC (P < .01) when compared to women who had IC. The overall cesarean rate in the CC group was 27.3%, versus 10.3% in the IC group. Clinical Implications: Intermittent catheterization only as needed appears to be best practice for bladder management for laboring women with an epidural. There was a significantly higher rate of cesarean birth among women in the CC group. The relationship between route of birth and use of continuous indwelling urinary catheters for women in labor with epidurals for pain relief needs more study. Abstract : Results of this randomized controlled trial should cause nurses to question routine use of indwelling catheters for women in labor who have epidural analgesia. As with many uncessary interventions, there may be unintended consequences.